ANALYSIS OF THE INFLUENCE OF HUMAN RESOURCE COMPETENCIES, INTERNAL CONTROL, ORGANIZATIONAL COMMITMENT, AND IMPLEMENTATION OF AGENCY-LEVEL APPLICATION SYSTEMS ON THE QUALITY OF GOVERNMENT FINANCIAL REPORTS - Jessi Febrianti; Erlina; Khaira Amalia Fachrudin (CV. Radja Publika, 2024)
This study aims to analyze and determine the effect of Human Resource Competencies, Internal Control, Organizational Commitment and Implementation of the Agency Level Application System (SAKTI) on the Quality of Government Financial Statements. The population in this study is the Indonesian Quarantine Agency. This research uses data. The data obtained through distributing questionnaires was then analyzed using SmartPLS tools. The results of the study at α 5% show that Internal Control has a significant positive effect on the Quality of Financial Statements, Organizational Commitment has a significant positive effect on the Quality of Financial Statements, Implementation of SAKTI has a significant positive effect on the Quality of Financial Statements, while Human Resource Competence has an insignificant positive effect on the Quality of Financial Statements, Practical implications increase the commitment of government agencies to provide competent personnel in their fields and Educational Institutions encourage the government to implement this. This research supports the theory proposed and there are still other factors outside this research model, and further research should use different tests and access more practical questionnaires.